An Unsymmetrical bis‐Imine Derivative for Solvent Dependent Rapid Optical Discrimination of Al3+, Zn2+ and OCl−: Combined Experimental and Theoretical Studies. Issue 8 (20th February 2023) - Shyam, Tandrim; Ghosh, Milan; Ghosh, Subhasis; Das, Debasis
Abstract: An unsymmetrical bis‐imine derivative (A2 ) selectively detect Al 3+, Zn 2+ and OCl − in a solvent dependent manner where Al 3+ and Zn 2+ emit green and blue light in DMSO−H2 O media while OCl − emits green‐yellow light in aqueous ethanol. The corresponding florescence enhancements are 8.2 fold, 3.7 fold (chelation enhanced fluorescence and excited state intra‐molecular proton transfer OFF) and 10.6 fold (H‐bonding, excited state intra‐molecular proton transfer OFF) respectively. While the limit of detection (LODs) for Al 3+, Zn 2+ and OCl − are 49 nM, 35 nM and 74 nM respectively, the corresponding binding/ association constants are 1.79×10 5 M −1, 1.8×10 5 M −1 and 3.68×10 5 M −2 . The results of density functional theory (DFT) studies are fairly close to that of experimental findings. Abstract : An unsymmetrical bis‐imine derived multi‐analyte sensor (A2) is capable for solvent dependent discrimination of Al 3+, Zn 2+ and OCl − at three different emission wavelengths, viz . 495 nm (λex =345 nm, aqueous‐DMSO), 450 nm (λex =345 nm, aqueous‐DMSO) and 503 nm (λex =350 nm, aqueous‐EtOH). The LODs of A2 for Al 3+, Zn 2+ and OCl − are 49 nM, 35 nM and 74 nM respectively.